Chickan Slaughter Mechanism In Realizing Halal Product Guarantee (Studi On The Light Lasinrang Chicken Slaughterhouse) - Abustani Ilyas; Muhammad Zaifuddin; Syarifuddin Syarifuddin (ITB AAS INDONESIA Surakarta, 2023)
Halalness of a product is a mandatory need for every consumer, especially Muslim consumers. In the international trade system, the issue of certification and marking halalness of products has received good attention in order to provide protection for Muslim consumers around the world as well as as a strategy to face the challenges of globalization. This study aims to find out how the process of slaughtering chickens in the Lasinrang Chicken Slaughterhouse and how the operational process of the Lasinrang Chicken Slaughterhouse in realizing the Halal Assurance System (SJH). The research methods used are qualitative with a femomenological approach, data sources used primary and secondary, methods of collecting interview data, observation, and documentation, data analysis techniques, namely data reduction, data presentation and conclusion drawing. The results of the study found that first, the process of slaughtering animals in the Ayam Lasinrang slaughterhouse is in accordance with the provisions of Shari'a through the method of using a sharp knife, facing the Qibla and always threatening bismillah every time you slaughter a chicken. Second, the Operational Process in realizing the halal assurance system at the chicken slaughterhouse in Lasinrang is still in the process stage because to have Halal certification, it must go through MUI supervision with a training model held by MUI regarding Halal certification to get Halal assurance system certification so that consumers can feel comfortable in buying a chicken cut.